2018
DOI: 10.1590/2237-6089-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder: an adaptation of the Taiwan short version of the screening inventory into Brazilian Portuguese

Abstract: Objective The current study presents the translation and adaptation of the 20-item Taiwan version of the Borderline Personality Inventory (BPI) into Brazilian Portuguese (BPI-P). Methods After translation and back-translation, the Brazilian Portuguese version was administered to three samples: patients with borderline personality disorder, psychiatric patients with comorbid substance use disorder and volunteers with no reported mental disorders. Results Significant differences between groups for borderline sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Related studies revealed that some brief screening tools, such as MSI, had multi-factor solution models [ 42 , 43 ]. Needless to say, the lengthier scales also had more than one factor [ 44 , 45 ], rendering the total score less legitimate because of its multidimensional construct [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related studies revealed that some brief screening tools, such as MSI, had multi-factor solution models [ 42 , 43 ]. Needless to say, the lengthier scales also had more than one factor [ 44 , 45 ], rendering the total score less legitimate because of its multidimensional construct [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lower levels of self-differentiation according to the Differentiation of Self Inventory (DSI-R) [57], and also higher levels of avoidant attachment according to the Experiences of Close Relationships Questionnaire (ECR-R) [58], were found in patients with anxiety disorders when compared to healthy controls [31]. Furthermore, correlations between anxiety symptoms and aspects of impaired personality functioning have been reported [59][60][61]. Interestingly, impaired personality functioning due to comorbid personality disorders has also been linked to treatment-resistance of anxiety disorders, and patients seem to pro t from intensi ed treatment taking into account aspects of personality functioning [62].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MSI or IPDE, the SI-Bord uses only the most important diagnostic criteria of BPD instead of using all 9 DSM criteria. As a screening tool, only those items that correlate strongly with the reference diagnosis were counted [28,41]. It is easier to form a unidimensional scale with only a few items, making it logical to use both the total score and cut-off score.…”
Section: Discussionmentioning
confidence: 99%